A fully reconfigurable bandpass‐to‐notch filter with wide bandwidth tuning range based on external quality factor tuning and multiple‐mode resonator. Issue 5 (3rd February 2019) - Lan, BoZhang; Qu, Yan; Guo, ChenJiang; Ding, Jun
Abstract: A fully reconfigurable microstrip bandpass‐to‐notch filter based on varactors is presented in this article. This filter offers wide center frequency and bandwidth tuning flexibility under bandpass mode and wide notch tuning range under notch mode. The entire tuning ability is based on multiple‐mode resonator (MMR) theory and tunable external quality factor for bandpass mode and the introduction of transmission zero (TZ) for notch mode. Under the bandpass mode, the center frequency tuning range is 0.9 to 1.42 GHz, and the bandwidth can be tuned from 0.09 to 1.44 GHz at a fixed center frequency 1.28 GHz. Under notch mode, the notch can be tuned from 0.98 to 2.02GHz. Good agreement can be observed between simulated and measured results.